Authoritarian Laughter : Political Humor and Soviet Dystopia in Lithuania - Klumbytė, Neringa, 1974- (Book collections on Project MUSE., 2022)
"This book explores the authoritarian state project to create an official humor culture in Soviet Lithuania in 1956-1984. It focuses on the satire and humor magazine Broom (Sluota), which created multidirectional laughter and was a forum for a critical public united in anti-Soviet revolutionary laughter in the late 1980s"--